TEGANGAN PERTUMBUHAN PERMUKAAN KAYU JABON UMUR 5 TAHUN DARI HUTAN RAKYAT DI SLEMAN, YOGYAKARTA - Ridho, Muhammad Rosyid; Marsoem, Sri Nugroho; Listyanto, Tomy; Sulistyo, Joko (JURNAL HUTAN LESTARI, 2024)
Burflower (Neolamarckia cadamba Miq.) is a fast-growing wood species which has been planted in some community forest on Java Island in recent years. This study aims to examine the surface growth stress of 5-year-old burflower wood from a community forest in Sleman, Yogyakarta. In addition, the axial variation of the surface growth stress within the stem also studied. The strain gauges method was conducted to determine the surface-released strains (SRS) in the stem periphery. The results show that the mean value of longitudinal SRS was -241,58 Î¼É› (-239 "“ 1.141 Î¼É›), while tangential SRS was -208,89 Î¼É› (-564 "“ 18 Î¼É›). These SRS values were considered low (under 650 Î¼É›) therefore the burflower wood theoretically has no potential for processing defects. There is no significant difference in SRS value within stem in the axial direction. This result indicates that the SRS measurement for 5-year-old burflower wood can be carried out only in the breast high of standing trees. Keywords: Periphery, processing-defects, strain gauges, strains Abstrak Jabon (Neolamarckia cadamba Miq.) adalah spesies kayu cepat tumbuh yang banyak ditanam di hutan rakyat di Pulau Jawa dalam beberapa tahun terakhir. Penelitian ini bertujuan untuk mempelajari tegangan pertumbuhan permukaan kayu jabon yang berumur 5 tahun dari hutan rakyat di Kabupaten Sleman, Yogyakarta. Selain itu, variasi aksial dari tegangan pertumbuhan dalam satu batang pohon juga dipelajari. Metode strain gauges digunakan untuk menentukan pelepasan regangan permukaan (PRP) pada periferi batang pohon. Hasil penelitian menunjukkan nilai rerata PRP longitudinal yaitu 241,58 Î¼É› (-239 "“ 1.141 Î¼É›), sedangkan PRP tangensial sebesar -208,89 Î¼É› (-564 "“ 18 Î¼É›). Nilai PRP yang relatif rendah (di bawah 650 Î¼É›) menunjukkan bahwa kayu jabon secara teori tidak berpotensi mengalami cacat pengolahan. Tidak ditemukan adanya perbedaan signifikan nilai PRP dalam satu pohon pada arah aksial. Hasil ini mengindikasikan bahwa pengukuran PRP pada kayu jabon umur 5 tahun cukup dilakukan pada bagian setinggi dada saja pada saat pohon masih berdiri. Kata Kunci: Cacat pengolahan, periferi, regangan, strain gauges